Strategi Inovasi Untuk Meningkatkan Pelayanan Perizinan Penelitian Asing - Bambang Herlambang (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Indonesia's natural and cultural riches have attracted the attention of foreign researchers to conduct research in Indonesia. Indonesia is considered to be one of the largest biological laboratories in the world, so there are many objects that can be used for research by foreign researchers. To provide research licensing services for foreign researchers who wish to conduct research in Indonesia, a legal basis was issued, namely Law No. 11 of 2019 concerning the National System of Science and Technology which regulates research licensing for foreign researchers in Indonesia. As a supporter of Law no. 11 of 2019, BRIN Regulation no. 22 of 2022 concerning Ethical Clearance has been issued. To provide foreign research licensing services according to Law No. 11 of 2019, it is carried out by the Directorate of Research and Innovation Licensing and Scientific Governance of the National Research and Innovation Agency (BRIN). To make it easier to apply for research permits for foreign researchers, several service improvements were made, namely the first was the formation of an ethics commission team to replace the TKPIPA team to evaluate incoming proposals. Second, the number of files that foreign researchers need to prepare is less than before, namely from 14 documents to 7 documents. Third, creating an ethical clearance website to upload the required files in digital form which was previously done offline and submitting hard copy files. Fourth, the addition of financial reporting features to make it easier to check payments and send research progress reports by foreign researchers.